Flow and heat transfer in geothermal systems : basic equations for describing and modeling geothermal phenomena and technologies - Tóth, Aniko; Bobok, Elemér, 1938- (Elsevier, 2017)
Flow and Heat Transfer in Geothermal Systems: Basic Equations for Description and Modeling Geothermal Phenomena and Technologies is the ideal reference for research in geothermal systems and alternative energy sources. Written for a wide variety of users, including geologists, geophysicists, hydro-geologists, and engineers, it offers a practical framework for the application of heat and flow transport theory. Authored by two of the world's foremost geothermal systems experts, whose combined careers span more than 50 years, this text is a one-stop resource for geothermal system theory and application. It will help geoscientists and engineers navigate the wealth of new research that has emerged on the topic in recent years.